A machine learning approach to analyze and predict rainfall in different regions of Bangladesh - Rahee, Arnob; Nafiz, Md. Montasir; Bhuiyan, Sania Azhmee (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.